Educating competitive technical university students in the conditions of the modern world; 11th International Technology, Education and Development Conference (INTED2017), 6-8 March, 2017, Valencia, Spain - Gil L. B. Ludmila Boleslavna; Demenkova L. G. Larisa Gennadievna; Ilyashchenko D. P. Dmitry Pavlovich; Chekhovskikh K. A. Konstantin Anatolievich; Ershova N. V. Nadezhda Viktorovna; Mamadaliev R. A. Rasul Akhmadovich (2017, 2017)
Title screen